The Influence of Good Corporate Governance on Earning Management on Manufacturing Company Listed In Indonesia Stock Excahange - Yosep Halomoan Sirait; Rina Br Bukit; Sambas Ade Kesuma (Jurnal Mantik, 2022)
This study aims to analyze the effect of good corporate governance on earning management in manufacturing company listed in Bursa Efek Indonesia for the period 2015 to 2020. The variables used in this study are managerial ownership, independent board of commissioners, institutional ownership, audit committee size and expertise. audit committee finance as an independent variable. Sampling using purposive sampling method, obtained a sample of 34 companies from 193 company populations with a total of 204 observations. The data used are the financial statements of each sample company, which are published through www.idx.co.id and www.invesnesia.com. The analytical method used in this study is a quantitative method, with classical assumption testing, as well as statistical analysis, namely multiple linear analysis. The results of the analysis show that simultaneously good corporate governance mechanisms, including managerial ownership, independent board of commissioners, institutional ownership, audit committee size and audit committee financial expertise have an effect on earning management. The results of the partial analysis show that the independent board of commissioners and the size of the audit committee have no effect on earning management, while managerial ownership, institutional ownership and financial expertise of the audit committee have a positive and significant effect on earning management.